PRODUCTIVE EMPLOYMENT AS THE BASIS OF THE MECHANISM OF ASSOCIATION AND THE ECONOMIC GROWTH AND SOCIAL DEVELOPMENT - Zova, V. A. (Science and Transport Progress, 2008)
The dependence of production employment efficiency and social and economic development is considered in this article.